2014
DOI: 10.3390/ijms16010284
|View full text |Cite
|
Sign up to set email alerts
|

The Anticancer Drug Ellipticine Activated with Cytochrome P450 Mediates DNA Damage Determining Its Pharmacological Efficiencies: Studies with Rats, Hepatic Cytochrome P450 Reductase Null (HRN™) Mice and Pure Enzymes

Abstract: Ellipticine is a DNA-damaging agent acting as a prodrug whose pharmacological efficiencies and genotoxic side effects are dictated by activation with cytochrome P450 (CYP). Over the last decade we have gained extensive experience in using pure enzymes and various animal models that helped to identify CYPs metabolizing ellipticine. In this review we focus on comparison between the in vitro and in vivo studies and show a necessity of both approaches to obtain valid information on CYP enzymes contributing to elli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 83 publications
0
26
0
Order By: Relevance
“…The main reason for the interest in ellipticine and its derivatives for clinical purposes is their high efficacy against several types of cancer (Auclair, 1987;Garbett et al, 2004;Kizek et al, 2012;Stiborova and Frei, 2014;Stiborová et al, 2011;2015a). The predominant mechanisms of ellipticine's biological effects were proposed to be intercalation into DNA (Auclair, 1987;Garbett et al, 2004;Tmejova et al, 2014) and inhibition of topoisomerase II (Auclair, 1987;Garbett et al, 2004;Kizek et al, 2012;Stiborova and Frei, 2014;Stiborová et al, 2011;2015a). We also showed that this antitumor agent forms covalent DNA adducts after metabolic activation by cytochrome P450 (CYP) enzymes and peroxidases (Stiborová et al, , 2003a2003b;2007a;2007b;2012b;Kotrbová et al, 2011), suggesting an additional DNA-damaging effect of ellipticine.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…The main reason for the interest in ellipticine and its derivatives for clinical purposes is their high efficacy against several types of cancer (Auclair, 1987;Garbett et al, 2004;Kizek et al, 2012;Stiborova and Frei, 2014;Stiborová et al, 2011;2015a). The predominant mechanisms of ellipticine's biological effects were proposed to be intercalation into DNA (Auclair, 1987;Garbett et al, 2004;Tmejova et al, 2014) and inhibition of topoisomerase II (Auclair, 1987;Garbett et al, 2004;Kizek et al, 2012;Stiborova and Frei, 2014;Stiborová et al, 2011;2015a). We also showed that this antitumor agent forms covalent DNA adducts after metabolic activation by cytochrome P450 (CYP) enzymes and peroxidases (Stiborová et al, , 2003a2003b;2007a;2007b;2012b;Kotrbová et al, 2011), suggesting an additional DNA-damaging effect of ellipticine.…”
Section: Introductionmentioning
confidence: 98%
“…We also showed that this antitumor agent forms covalent DNA adducts after metabolic activation by cytochrome P450 (CYP) enzymes and peroxidases (Stiborová et al, , 2003a2003b;2007a;2007b;2012b;Kotrbová et al, 2011), suggesting an additional DNA-damaging effect of ellipticine. This DNA damage has been found to be the major mechanism of ellipticine's antitumor activities 2012b;2014b;2015a;Stiborova and Frei, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deoxyribonucleic acid (DNA), specifically, comprises a variety of nucleophilic foci at which these DNA-damaging agents can form DNA adducts through at least one covalent bond [24,25]. CYP-mediated reactions can be used to examine the potential of chemicals to be activated to form reactive species, leading to the formation of covalent DNA adducts [26][27][28].…”
mentioning
confidence: 99%